Psychological Distress and Resilience as Predictors of Grit in the Sandwich Generation - Khesya Margarita Kase Lie; Arthur Huwae (Kuras Institute, 2026)
The Sandwich Generation refers to individuals who simultaneously bear dual responsibilities, namely caring for elderly parents while raising children, which potentially exposes them to varying levels of psychological distress. This study aimed to examine the roles of psychological distress and resilience in predicting grit among the Sandwich Generation in Indonesia. Employed a quantitative approach with a linear regression design. The participants consisted of 400 individuals from the Sandwich Generation, selected through purposive sampling. The research instruments included the Kessler Psychological Distress Scale (K10), Connor-Davidson Resilience Scale (CD-RISC), and Short Grit Scale (Grit-S). The results supported the central hypothesis and the first minor hypothesis, but did not support the second minor hypothesis. Psychological distress and resilience jointly had a significant effect on grit among the Sandwich Generation in Indonesia (F = 4.556; p = 0.011). Partially, psychological distress significantly predicted grit (β = -0.100; t = -2.589; p = 0.010), while resilience did not show a significant effect on grit (β = 0.030; t = 1.614; p = 0.107). These findings highlight the importance of designing interventions that focus on adaptive management of psychological distress to sustain long-term perseverance among the Sandwich Generation. In contrast, resilience remains crucial as a buffer for emotional stability, even though it does not directly enhance grit.